PLTS Hybrid Power Plant Design – 3000 VA Fuel Generator in the Tourism Village of Cilintung Garut Village - Imran Al Hafiz; Teguh Arfianto; Waluyo Waluyo (Institut Teknologi Nasional, Bandung, 2022)
This study discusses the design of a 3000 VA PLTS-BBM hybrid power generation system in the tourist village of Kampung Cilintung Situgede Karangpawitan Garut. This is necessary because an energy tourism area will be built there, and it requires an adequate supply of electricity. PLTS is the main electricity supplier combined with the uses of fuel generators to harnest solar radiation in the area. The determination of the initial power energy requirement is 3000 VA or 2550 watts for 18 hours of use so that the energy required is 45900 Wh. The rating of the device used is 48 V. The number of solar panels are 14 panels connected in series-parallel, using 24 units of battery. The generator used is a gasoline generator with a four-stroke engine having a capacity of 3000 W with an electrical output of 220 V AC. The design process also makes use of the PVSyst application. The design of this solar module will be realized in form of a powerhouse to supply the entire tourist village area.